Tupperware Malaysia / Fatin Nabila Mohd Sahidin - Mohd Sahidin, Fatin Nabila (2021)
This report of the social media portfolio is an individual project that need each of students to set up new business, which is a real entrepreneurial business and, we have to use a social media platform which is Facebook for marketing purposes. For this project, I have chosen the Tupperware Brands as my business because I’m sure that this product can help people to solve their problem help them to get a job. In Tupperware, they provide many products to make it easier in your life. It also the most popular brands in the world that has warranty lifetime and easy to sell it.